Effect of a Self-Care Educational Program Based on Orem\'s Model on Stress in Patients Undergoing Hemodialysis - Fatemeh Rostami; Farhad Ramezani Badr; Koorosh Amini; Aub Pezeshki (Zanjan University of Medical Sciences and Health Services, 2015)
Background and Objectives: Stress is a common and important psychological problem among patients undergoing hemodialysis. Stress can negatively affect the quality of life, treatment acceptance, and disease progress in patients. Participation of patient in self-care activities lead to more independence and patients adjustments with their illnesses. The aim of this study was to determine the effect of a self-care educational program based on the Oremchr('39')s model on stress in hemodialysis patients. Materials and Methods: This semi-experimental pretest-posttest study was conducted in the educational hospitals affiliated to Zanjan University of Medical Sciences. Participants were selected among from patients undergoing hemodialysis through convenience method and were allocated into two intervention and control groups using blocked randomization. After baseline measurement, the educational program was implemented in the intervention group for 30-minutes weekly sessions. Stress was measured before and one month after the intervention in both groups using the stress part of the DASS-42 questionnaire. The data were analyzed in the SPSS-19 using descriptive statistics, paired-t test, independent t-test, and chi-squared test. Results: The mean age of the participants was 55.13±15.1 years. Most of the participants were male (63.3%), 76.0% were married and 47.88% had not finished the high school. There was a significant decrease in the mean stress score after the intervention (P<0.001). There was also a significant difference in the mean of stress score between the two groups after the intervention (p=0.03). Conclusion: According to the positive effect of our educational program designed based on the Oremchr('39')s self-care model, it seems that the program could be implemented to decrease stress in patients undergoing hemodialysis.